Electrochemical Performance and Hydrogen Storage of Ni–Pd–P–B Glassy Alloy - Ahmed Alshahrie; Bassim Arkook; Wafaa Al-Ghamdi; Samah Eldera; Thuraya Alzaidi; Hassan Bamashmus; Elsayed Shalaan (Nanomaterials, 2022)
The search for hydrogen storage materials is a challenging task. In this work, we tried to test metallic glass-based pseudocapacitive material for electrochemical hydrogen storage potential. An alloy ingot with an atomic composition of Ni60Pd20P16B4 was prepared via arc melting of extremely pure elements in an Ar environment. A ribbon sample with a width of 2 mm and a thickness of 20 mm was produced via melt spinning of the prepared ingot. Electrochemical dealloying of the ribbon sample was conducted in 1 M H2SO4 to prepare a nanoporous glassy alloy. The Brunauer–Emmett–Teller (BET) and Langmuir methods were implemented to obtain the total surface area of the nanoporous glassy alloy ribbon. The obtained values were 6.486 m2/g and 15.082 m2/g, respectively. The Dubinin–Astakhov (DA) method was used to calculate pore radius and pore volume; those values were 1.07 nm and 0.09 cm3/g, respectively. Cyclic voltammetry of the dealloyed samples revealed the pseudocapacitive nature of this alloy. Impedance of the dealloying sample was measured at different frequencies through use of electrochemical impedance spectroscopy (EIS). A Cole–Cole plot established a semicircle with a radius of ~6 Ω at higher frequency, indicating low interfacial charge-transfer resistance, and an almost vertical Warburg slope at lower frequency, indicating fast diffusion of ions to the electrode surface. Charge–discharge experiments were performed at different constant currents (75, 100, 125, 150, and 200 mA/g) under a cutoff potential of 2.25 V vs. Ag/AgCl electrode in a 1 M KOH solution. The calculated maximum storage capacity was 950 mAh/g. High-rate dischargeability (HRD) and capacity retention (<semantics>Sn</semantics>) for the dealloyed glassy alloy ribbon sample were evaluated. The calculated capacity retention rate at the 40th cycle was 97%, which reveals high stability.